USE OF THE BLOCKCHAIN CONCEPT IN THE PERFORMANCE OF CONTRACTUAL OBLIGATIONS - Hulicki, Maciej; Lustofin, Paweł (Człowiek w cyberprzestrzeni, 2020)
We are now living in the digital revolution, also referenced by some as the digital transformation. It would not have develop was it not for the technical tools for data transfer, processing speed and availability of mobile devices. At present, the greatest hope is placed in such techniques and technologies as: Internet of things, 3D printing, augmented reality, artificial intelligence and machine learning, big data, coupled with the concept of distributed databases in the form of blockchain, which tends to come under the name of disruptive innovation - the subject matter hereof. All these technical tools imply major changes in our daily environment and are, at the same time, highly complex. We believe this calls for a thorough legal analysis.